1992
DOI: 10.1180/claymin.1992.027.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Weathering of biotite to vermiculite in Quaternary lahars from Monti Ernici, Central Italy

Abstract: A B S T R A C T:The weathering of biotite in Quaternary lahars from Monti Ernici (Central Italy) via interstratification stages has been studied by X-ray diffraction of both the interstratified minerals and the initial (biotite) and final (vermiculite) end-members. The structure of the biotite and vermiculite is described by means of monodimensional Fourier series. The interstratified phases have been studied using the INTER program which permits an analysis of two interstratified components by Fourier transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 4 publications
4
13
0
Order By: Relevance
“…These authors found out that even small samples are normally characterized by different spatial concentrations of biotite, vermiculite and an intermediate interstratified phase in dependency to the alteration grade. Our results for the geochemical mass balance (Table 2) as element losses or gains and total loss of mass of the bioweathered biotite zone were in good agreement with data obtained by Pozzuoli et al (1994) and suggest the transformation biotite to scarcely altered biotite with a biotite-vermiculite intermediate interstratified phase. However, additional work remains to be done to confirm the occurrence of this mineralogical transformation of biotites in the lichen-mineral interface.…”
Section: Discussion a N D C O N C L U S I O N Ssupporting
confidence: 78%
See 3 more Smart Citations
“…These authors found out that even small samples are normally characterized by different spatial concentrations of biotite, vermiculite and an intermediate interstratified phase in dependency to the alteration grade. Our results for the geochemical mass balance (Table 2) as element losses or gains and total loss of mass of the bioweathered biotite zone were in good agreement with data obtained by Pozzuoli et al (1994) and suggest the transformation biotite to scarcely altered biotite with a biotite-vermiculite intermediate interstratified phase. However, additional work remains to be done to confirm the occurrence of this mineralogical transformation of biotites in the lichen-mineral interface.…”
Section: Discussion a N D C O N C L U S I O N Ssupporting
confidence: 78%
“…The geochemical mass balance data showed in Table 2 indicates that loss of Fe as total Fe was observed. The application of microprobe analysis does not perrnit determination of the valence of the Fe cations, but according to Pozzuoli et al (1994) more intensive decreases in Fe 2+ than gains in Fe 3 § during the first stage of natural weathered biotite can be suspected. Moreover, an increase in Ca 2 § and Na § in the interlaminar spacing was observed.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
See 2 more Smart Citations
“…The program allows diffraction effects to be calculated from given mixtures (XRD Intensity Function) and compared with experimentally recorded diffraction curves. This program was also used to calculate the distribution function of interlayer distances, W(R), by the direct Fourier transform method (Martfn de Vidales et al 1990;Arag6n de la Cruz et al 1992;Pozzuoli et al 1992;Ruiz-Amil et al 1992;Ruiz-Amil et al 1993). …”
Section: Calculation Of the Distribution Function Of Interlayer Distamentioning
confidence: 99%